The Effect of Hand Paddle Training on 50 Meter Freestyle Swimming Speed in Beginner - Iyakrus Iyakrus; Silvi Aryanti; Arizky Ramadhan; Guli Septi Ariski (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
The purpose of engaging in the look at was to decide the effect of hand paddle exercise on the rate of 50 meter freestyle swimming in novice swimmers. This research technique makes use of a quasi-experimental method, which means that before being given this design treatment, it uses pretests. The studies design used is one group pretest-posttest design. The usage of the full sampling technique for sampling 30 people. The research instrument is that the entire sample performs a 50 meter freestyle swimming test. From the outcomes of records processing and evaluation using the facts normality check, hypothesis take a look at with the t test formulation, that exercises using hand paddle have an influence on 50 meters freestyle swimming speed. It may be seen from the results of statistics evaluation thru the calculation of the t-test formula with the criteria tcount (13.730) > ttable (1.70) with a belief level of 0.95 or 95% (α=0.05) and the quantity of samples (N = 30). Then the proposed speculation is ordinary. Training using hand paddle aids in the water really has an effect on 50-meter freestyle swimming speed. Based on the results of research on the effect of training using hand paddle aids which are thought to have an influence on 50-meter freestyle swimming speed, it turned out to have a significant influence on speed in 50-meter freestyle swimming at in novice swimmers of the pusri club. The implication of this study is that exercises using hand paddle aids can be done and used as an exercising program to improvement swimming speed in novice swimmers.